FRI0541 Imaging of Chronic Recurrent Multifocal Osteitis: A French National Cohort of 178 Cases. (10th June 2014) - Wipff, J.; Nouar, D.; Lemelle, I.; Pajot, C.; Duquesne, A.; Lorrot, M.; Faye, A.; Bader-Meunier, B.; Brochard, K.; Despert, V.; Jean, S.; Grall-Lerosey, M.; et al.
Abstract : Background: The radiological assessment of CRMO is currently the subject of countless works and the recent use of whole-body MRI leads to discuss the respective roles of the various imaging techniques. Objectives: This study provides a descriptive evaluation of imaging OCMR, its diagnostic management and a comparison between different techniques. Methods: 178 CRMO patients were included (123 females and 55 males). The lesions detected by imaging (plain radiographs, isotopic bone scan and/or MRI) were collected by specifying the number, location (bone, proximal/distal and metaphyseal/epiphyseal/diaphyseal), character (lytic/sclerotic/mixed) and the signal MRI T1 and T2 (hypo/hyper). Results: A total of 193 radiographic lesions were detected with the following distribution: tibia (n=44), the clavicle (n=34), the femur (n=23), the fibula (n=20) and pelvis (n=19). The lesions of the lower limbs accounted for 52% of the lesions. The lesions of the long bones were most often located in metaphyseal (58/76, 76%) and were lytic in 76/162 (47%) and sclerotic in 60/162 (37%). The isotopic bone scan detected 372 lesions localized to the pelvis (n=64), tibia (n=51), femur (n=44), clavicle (n=40) and vertebrae (n=29). The lesions of the pelvis were mainly in iliac bones (73%), proximal at clavicles (78%) and femur (57%), but distal at tibia (53%) and fibula (88%). Whatever the location of the long bones, the lesions were most often metaphyseal (65/92, 56%). MRI detected 515 lesions distributed as follows: pelvis (n=100), tibia (n=93) and femur (n=73). 51 vertebral lesions (10%) were detected in 36 patients. Most of them were localized at the thoracic level. The vast majority of lesions (98%) were hypo-T1 and hyper-T2. MRI showed metaphyso-epiphyseal and metaphyso-diaphyseal lesions usually undetectable in isotopic bone scan. Imaging has allowed confirming the multifocal pattern in 26/54 patients with clinical monofocal at the beginning of the disease. Of the remaining 28 patients with monofocal lesion at diagnosis, imaging contributed to confirm the multifocal pattern in 16 additional cases: a total of only 12 patients (7%) kept a pure monofocal evolution. In 15 patients, scintigraphy and whole-body MRI were performed at the same time (±3 months). Analysis of these 15 patients showed a higher sensitivity to detect lesions by MRI (6.7±3.1 vs 3.4±2.4, p=0.003) and better localization of lesions. Clinical chronic non bacterial osteitis (CNO) score was interpretable in 110 patients: the application of this score would have, in this cohort, to avoid 27/110 biopsies. Conclusions: The study of imaging in this large CRMO French cohort confirms the interest of imaging to characterize multifocal involvement of CRMO and help prevent invasive procedures for diagnostic purposes. MRI confirms its sensitivity to detect more lesions including spinal and pelvis than isotopic bone scan. MRI provided a more detailed description of the location of the lesions. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5337